Polyarylate based thin film composite (TFC) membranes: effects of coating parameters, gutter layer, and intrinsic material properties - Chendake, Yogesh J.; Bhole, Yogesh S.; Lohokare, Harshada R.; Kharul, Ulhas K. (Separation Science and Technology, 2010)
Investigations in thin film composite (TFC) membrane formation with polyacrylonitrile ultrafiltration membrane as a support and three polyarylates with sequentially increased polarity are reported. Effects of TFC membrane preparation parameters viz., concentration of the coating solution, dip time, presence of solvent in pores of UF membrane support, and presence of the gutter layer were examined towards the formation of the selective skin layer, which was assessed by gas permeation analysis. TFC membranes prepared using dimethyl bisphenol-A based polyarylate exhibited similar to 3 orders of magnitude higher permeability and comparable selectivity as that of its dense membrane.
Keywords: Gas permeation; gutter layer; polarity; polyarylates; TFC membrane

Binary mixtures of aprotic and protic ionic liquids demonstrate synergistic polarity effect: an unusual observation - Thawarkar, Sachin; Khupse, Nageshwar D.; Kumar, Anil (Journal of Solution Chemistry, 2020)
In this communication, we demonstrate the solute-solvent and solvent-solvent interactions in the binary mixtures of two aprotic ionic liquids, namely 1-butyl-3-methylimidazolium bis(trifluoromethylsulfonyl)imide and 1-butyl-1-methylpyrrolidinium bis(trifluoromethylsulfonyl)imide, with the protic ionic liquid 1-methylimidazolium acetate. The synergistic effects as expressed by the solvatochromic parameter are noted. This observation is in contrast to the mixing of protic ionic liquids 1-methylpyrrolidium acetate and 4-methylmorpholine acetate with 1-methylimidazolium acetate, respectively. It appears that the synergistic effects in the binary mixtures of aprotic and protic ionic liquids are caused by the formation of hydrogen bonds, since cations are dominant H-bond donors while anions are dominant H-bond acceptors. Preferential solvation models are used to describe the solute-solvent interactions in the binary ionic liquid mixtures.
Keywords: binary mixture; Ionic liquid; polarity; Preferential solvation; synergetic effect